Evaluation of an Internal Review Process for Grants And Manuscripts in the Canadian Critical Care Trials Group - Karen EA Burns; Elaine Caon; Peter M Dodek (Canadian Respiratory Journal)
RATIONALE AND OBJECTIVES: All grants and manuscripts bearing the Canadian Critical Care Trials Group name are submitted for internal peer review before submission. The authors sought to formally evaluate authors’ and reviewers’ perceptions of this process.